The role of ferritin in enhancing the stress tolerance of grapevine - Kós Péter B.; Hungarian Congress on Plant Biology, 9., 2008, Szeged (2008)
In order to improve the stress tolerance of grapevine, transgenic plants were produced and regenerated from the anthers of a grapevine rootstock cultivar expressing the ferritin of Medicago sativa. Leaf disks of the plants were exposed to oxidative stress by intracellular ROS production using paraquat, a herbicide known to mediate superoxide radical formation in thylakoid membranes. The Medicago ferritin had a high expression level in the transgenic plants under normal condition, and it further increased about twofold under the applied stress condition. In response to the treatment, the transgenic plants showed enhanced stress tolerance as compared to the untransformed cultivar.